Surface integrity in metal machining - Part II: Functional performance - la Monaca, Andrea; Murray, James W.; Liao, Zhirong; Speidel, Alistair; Robles-Linares, Jose A.; Axinte, Dragos A.; Hardy, Mark C.; Clare, Adam T. (Elsevier Ltd, 2021)
Material removal operations play a pivotal role in the manufacture of key components, required for engineering systems to operate safely and efficiently under ever more advanced functional requirements and over extended life cycles. To further step up the loading capability of machined parts, fundamental understanding of how of machining-induced features can influence the performance of advanced materials under complex service conditions is necessary over finer temporal and spatial scales. As discussed in Part I of this review, when engineering surfaces are generated by material removal processes, a wide range of physical mechanisms (e.g. mechanical, thermal, chemical and their combinations) drive the characteristics of workpiece surface integrity. In Part II of this review, the interplay between the metallurgical and micro-mechanical condition induced by material removal processes and their in-service response will be thoroughly explored, by a critical analysis of the state-of-the-art in the field. Specifically, attention is focused on recent advances made towards the understanding of the mechanisms determining the resistance of machined surface to fatigue crack nucleation (Section 2), corrosion and stress-corrosion cracking (Section 3), and wear (Section 4). Furthermore, the impact of relevant post-machining treatments on the in-service behaviour of machined surfaces is analysed, and the possible strategies for the enhancement of the functional performance of machined surfaces are presented (Section 5). Finally, the current research gaps and the prospective challenges in understanding the in-service behaviour of machined surfaces are critically discussed, providing an interpretation of the possible directions of future scientific development of this field.